The lost children - Dickson, Shirley (New York, NY : Forever, 2022)
"England, 1943: Home is no longer safe for eight-year-old twins Molly and Jacob. Night after night, wailing bombs and screeching planes skim the rooftops overhead. Their mother, Martha, has no choice but to evacuate them to the safety of the countryside, even if it means she might never see them again. At the train station, she gives Jacob a letter, telling him only to read it if they are in danger. In the country, Molly and Jacob must adjust to life with strangers. But then the unimaginable happens. Martha is killed in an explosion, leaving the twins all alone in the world. Motherless and destitute, the siblings face the grim reality of life in an orphanage. The time has finally come for Jacob to open the letter. What secret does it hold, and could it change the course of their tragic fate? Because if they are together, they can survive anything--but what if they are torn apart?" --Amazon.
"A World War II novel" -- Cover.
"Originally published in 2020 by Bookouture, an imprint of StoryFire Ltd." -- Title page verso.
Keywords: 1939-1945; Orphans -- England -- Fiction; Twins -- Fiction; Letters -- Fiction; World War, 1939-1945 -- Great Britain -- Fiction; Letters; Orphans; Twins; England; Great Britain; Historical fiction; Fiction; War fiction; War fiction